Risk Management Assessment in Iranian Banking based on IFSB Guidelines - Majid Feyz Arefi; Maryam Hafezian (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aimed to evaluate Islamic banking risk management based on IFSB guidelines in one of the state-owned banks in North Khorasan province.Methodology: The study is a descriptive survey, and the statistical population included branch employees, employees, and managers of different management departments of the bank. Sampling was random; the data collection tool was a questionnaire filled by 35 participants. The questionnaire used in this study is a translation of the questionnaire presented by Rosman and Abdul Rahman [30] based on the principles of the IFSB guide in 2015, the validity of which was confirmed by experts. Some editing points were applied, and its reliability was confirmed by 25 experts, with alpha Cronbach at 0.76. Descriptive statistics and Kolmogorov-Smirnov, binomial, and Friedman tests were used to analyze the data.Findings: The results showed that 9 out of 42 components of risk management are not in good condition, including two components of investment risk management, four of market risk management, one of liquidity risk management, and two of business risk management shift.Originality/Value: The study showed weaknesses and opportunities for improvement in market risk management, investment risk management, business transfer risk management, and liquidity risk management, respectively.